Indigenous perspectives on breaking bad news: ethical considerations for healthcare providers. Issue 12 (8th January 2021) - Cassim, Shemana; Kidd, Jacquie; Keenan, Rawiri; Middleton, Karen; Rolleston, Anna; Hokowhitu, Brendan; Firth, Melissa; Aitken, Denise; Wong, Janice; Lawrenson, Ross
Abstract : Most healthcare providers (HCPs) work from ethical principles based on a Western model of practice that may not adhere to the cultural values intrinsic to Indigenous peoples. Breaking bad news (BBN) is an important topic of ethical concern in health research. While much has been documented on BBN globally, the ethical implications of receiving bad news, from an Indigenous patient perspective in particular, is an area that requires further inquiry. This article discusses the experiences of Māori (Indigenous peoples of New Zealand) lung cancer patients and their families, in order to investigate the ethical implications of receiving bad news. Data collection occurred through 23 semistructured interviews and nine focus groups with Māori lung cancer patients and their families in four districts in the Midland Region of New Zealand: Waikato, Bay of Plenty, Lakes and Tairāwhiti. The findings of this study were categorised into two key themes: communication and context. Avenues for best practice include understanding the centrality of the HCP–patient relationship and family ties in the healthcare journey, and providing patients with the full range of viable treatment options including hope, clear advice and guidance when the situation calls for it. Overall, the findings of this study hold implications for providing culturally safe and humanistic cancer care when BBN to Māori and Indigenous patients.